Pengaruh Profitabilitas, Ukuran Perusahaan Dan Likuiditas Terhadap Struktur Modal Perusahaan Manufaktur Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2021 - Salim, Noor Salim; Khalimah, Siti (Accounting Study Program, Faculty of Economics and Business, 2023)
ABSTRACT Capital structure is a comparison on between a company’s long-term debt and its own capital in a company. There are several factors than can affect the capital structure, some of which are Profitability, Company Size, and Liquidity. The purpose of this study was to determine the effect of Profitability, Company Size and Liquidity on the Capital Structure of Food and Beverages Manufacturing Companies Listed on the Indonesian Stock Exchange in 2018-2021. The population of this study is all Food and Beverages Sub Sector companies listed on the the Indonesian Stock Exchange for the period 2018-2021. The method used for sampling is purposive sampling and obtained as many as 20 food and beverage company. The data analysis technique used is multiple linear regression analysis with the help of SPSS application. The result of this study indicate that: 1)Profitability, company size and liquidity have a simultaneous effect on capital structure, 2) Profitability has a negative and significant effect on capital structure partially, 2) Company Size has a positive and significant effect on capital structure partially, 3) Liquidity has a negative and significant effect on capital structure partially.